High performance communication system based on generic programming - Sanches, A. L. G.; Secco, F. R.; Frohlich, A. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
This paper presents a high performance communication system based on generic programming. The system adapts itself according to the protocol being used on communication, simplifying the development of libraries. In order to validate the concepts, a MPI implementation has been developed and it is compared to a traditional implementation - MPICH-GM. It is demonstrated that the same functionality and interface can be offered with similar performance, but with much less programming effort. That is evidence that the large size of traditional MPI implementations is due to the limitations of conventional communication systems.